Protocolo de avaliação em motricidade orofacial para Síndrome de Down - Ramos, Ariane de Assis (2019)
Objective: To present an assessment protocol in Orofacial Motricity aimed at people with Down Syndrome based on a literature review. Research strategy: Performed a bibliographic survey in the databases Scielo-Brazil, Medline/Pubmed, LILACS and Scopus. Twenty articles were analyzed for a qualitative integrative review. Selection: Complete studies were included, published between 2009 and 2019. Proposal development: The protocol developed consists of 5 parts: Identification, past history, global and structural assessment, functional assessment and speech assessment. Conclusion: The Orofacial Motricity Assessment Protocol for Down Syndrome was created from a literature review and depends on its application by different professionals in the target audience to be tested and validated.